The Role of Self-Efficacy on Academic Stress with Optimism as a Moderating Variable: Case Study in the Post-Covid-19 Higher Education Sector - Safitri, Irma; Yundianto, Devie; Ar-Rafi, Dimas (Universitas Pendidikan Ganesha, 2024)
One of the obstacles that become a concern in the world of education is academic stress because student expectations still need to be achieved in learning with the reality of learning that occurs. The purpose of this study was to determine the role of self-efficacy on academic stress with optimism. This research is a cross-sectional quantitative research with ex post facto method. The sampling technique used is convenience sampling. Respondents totaled 113 people with questionnaires as a method and instrument of data collection. The data analysis technique used is inferential statistical analysis. The results showed that there was no relationship between academic self-efficacy and optimism, as well as academic stress. In the variable relationship with the academic stress dimension, academic self-efficacy is associated with learning pressure and hopelessness. There is also a significant effect of academic self-efficacy on academic stress, and optimism has a significant effect on academic stress. This suggests a significant influence on both variables predictors of academic stress, confirming that optimism cannot be used as a moderator between academic self-efficacy and educational stress. This research provides valuable implications in efforts to improve post-COVID academic stress management, by providing a deeper understanding of the role of self-efficacy and optimism in managing such stress